Lupus-anticoagulant testing at NOAC trough levels - Ratzinger, Franz; Lang, Mona; Belik, Sabine; Jilma-Stohlawetz, Petra; Schmetterer, Klaus G.; Haslacher, Helmuth; Perkmann, Thomas; Quehenberger, Peter (Thrombosis and Haemostasis, 2016)
Non-vitamin K antagonist oral anticoagulants (NOAC), including rivaroxaban, apixaban or dabigatran, regularly show relevant effects on coagulation tests, making the interpretation of results difficult. The aim of this study was to evaluate possible interferences of NOACs in trough level concentrations in lupus anticoagulant (LA) testing. Citrate plasma specimens of 30 healthy volunteers were spiked with rivaroxaban, apixaban or dabigatran in four plasma concentration levels at or below trough NOAC levels. The NOAC concentration was measured using dedicated surrogate concentration tests and a stepwise diagnostic procedure for LA-testing was applied using screening, mixing and confirmatory testing. Results were compared to NOAC-free specimens. Starting with a plasma concentration of 12.5 ng/ml, dabigatran-spiked specimens showed significant prolongations in the lupus anticoagulant-sensitive activated partial thromboplastin time (aPTT-LA) as well as in the Dilute Russell viper venom time (dRVVT), leading to 43.3% false positives in confirmatory testing in the dRVVT. In contrast, rivaroxaban, beginning with 7.5 ng/ml, exclusively affected dRVVT-based tests. In confirmatory tests, 30.0% of rivaroxaban-spiked specimens showed false positive results. Starting with 18.75 ng/ml apixaban, a significant prolongation of the dRVVT and up to 20.7% false positives in confirmatory tests were found. In contrast to other NOACs tested, apixaban did not present with a dose-dependent increase of the dRVVT ratio. In conclusion, the rate of false positive results in LA-testing is unacceptably high at expected trough levels of NOACs. Even at plasma concentrations below the LLOQ of commercially available surrogate tests, LA testing is best avoided in patients with NOAC therapy.
Keywords: Coagulation; lupus anticoagulant; anticoagulant; non-vitamin K antagonist oral anticoagulants; laboratory testing